Potential of Deer Placenta Extract in Hair Cell Regeneration and Its Nanoniosome-Microspicule Gel as a Transfollicular Delivery System - Worranan Rangsimawong; Sureewan Duangjit; Phaijit Sritananuwat; Tanasait Ngawhirunpat; Praneet Opanasopit (Cosmetics)
Background: Deer placenta extract (DPE), rich in bioactive macromolecules, promotes regenerative effects in both normal and damaged cells. However, effective delivery of these macromolecules through the skin remains a challenge. Objectives: To investigate the potential of DPE in regenerating hair cells and to develop a nanoniosome (NS) and microspicule (MS) formulation as a promising transfollicular delivery system. Methods: The bioactivity of DPE was assessed in human follicle dermal papilla (HFDP) cells, including cells damaged by chemotherapy. The NS-MS formulation was designed to deliver biomacromolecules from DPE into skin and hair follicles. Results: DPE at 2000 µg/mL exhibited no cytotoxicity and significantly enhanced proliferation in both normal and cisplatin-treated HFDP cells. The DPE-loaded NSs displayed nanovesicles with a uniform size distribution and a negative surface charge. When incorporated into the MS gel, NS-MS demonstrated a synergistic effect, significantly enhancing the transdermal and transfollicular delivery of macromolecular protein into the skin layers and hair follicles. Conclusions: DPE promoted hair cell proliferation and facilitated the recovery of hair cells damaged by chemotherapy, especially when formulated into the NS-MS system, which effectively delivered bioactive macromolecules to the target site. This suggests its potential role in promoting hair regrowth.